Acércate a las brasas para ver los que dices (2020)
The recovery of the oral memory of the Colombian Pacific supposes, in addition to a coarse ethnographic task, an interesting polysemic undertaking, since in it the knowledge and traditions of orality converge together with a very significant theatricalization in which we must go beyond our place as readers. , this to get closer to the embers and share an imaginary full of music and symbolism. In one of those brief conversations held with the teacher Baudilio Revelo Hurtado about this new compilation of his work, the anecdote that would incidentally give the book its title appeared, “come closer to the embers to see what you say”, precisely as an example of what which means hearing first-hand that accumulation of anecdotes, stories and narratives of Afro-orality as a framework of a culture vitally linked to its territory and its roots.